Performance of Salvinia molesta plants in tertiary treatment of domestic wastewater - Mustafa H.M.; Hayder G. (Elsevier Ltd, 2023)
The objective of this study was to investigate the performance of different weight of Salvinia molesta plants in biological treatment of domestic wastewater. Three treatment systems containing 280g (GS1), 140g (GS2) and 70g (GS3) of S. molesta plants were used for the phytoremediation process. Physicochemical analysis such as pH, colour, chemical oxygen demand (COD), and biological oxygen demand (BOD5) of the influent and effluent water samples were performed according to spectrophotometric methods. The outcome of the study demonstrated that the different weight of S. molesta plants played a significant role in improving the quality of the wastewater samples, in which GS1 removed 96.8% (colour), 91% (BOD5), and 82.6% (COD). While up to 88.6% (colour), 87.1% (BOD5), and 81.1% (COD) reduction was observed for GS2 treatment systems, and GS3 was efficient in removing 85.5% (colour), 86.1% (BOD5), and 68.3% (COD). Also, a pH value of 6.297.19, 5.977.07, and 6.177.42 was obtained from GS1, GS2 and GS3 treatment systems, respectively. Thus, the treatment system with the highest quantity of S. molesta (GS1) demonstrated better performance compared to the other two systems (GS2 and GS3). The findings of this research can be applied in addressing the goals of sustainable development through the use of green technology to reduce the threat of water pollution in natural water bodies. Perhaps existing and future water scarcity can be resolved through the use of phytoremediation technology. 2021pH, chemical oxygen demand (COD), colour, biological oxygen demand (BOD5), hydroponic tanks, biological treatment method. 2021